2006
DOI: 10.1002/ajmg.a.31086
|View full text |Cite
|
Sign up to set email alerts
|

High heritability of fingertip arch patterns in twin‐pairs

Abstract: The presence of an arch pattern on at least one fingertip has previously been suggested as an autosomal dominant trait with reduced penetrance, although the examination of pedigrees with this trait segregating is also consistent with major gene or multifactorial inheritance. We utilized fingerprints in 2,484 twin-pairs to estimate heritability for the presence of at least one fingertip arch pattern. The frequency of arches in the entire sample was 4.3% (2,175/50,850), 5.5% in females and 3.2% in males. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…There is little information about the chorionicity in studies of dermatoglyphic heritability, for example, in relation to ridge counts (Reed et al, 1978), a-b ridges counts (Bogle et al, 1994) and arch pattern (Reed et al, 2006). The Reed et al (1978) study indicated that there was no chorionicity influence on the twin method in relation to left-hand thumb, since no significant difference between MCMZ and DCMZ twins was observed, whereas for the right hand thumb there was a significant difference between MCMZ and DCMZ twins and a chorionicity influence could occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little information about the chorionicity in studies of dermatoglyphic heritability, for example, in relation to ridge counts (Reed et al, 1978), a-b ridges counts (Bogle et al, 1994) and arch pattern (Reed et al, 2006). The Reed et al (1978) study indicated that there was no chorionicity influence on the twin method in relation to left-hand thumb, since no significant difference between MCMZ and DCMZ twins was observed, whereas for the right hand thumb there was a significant difference between MCMZ and DCMZ twins and a chorionicity influence could occur.…”
Section: Discussionmentioning
confidence: 99%
“…The digital dermatoglyphics used for one of the most mature biometric technologies (fingerprints) have their general characteristics determined mainly by genes (Holt, 1960;Jain et al, 2002;Reed et al, 2006;Reed & Young, 1982;Sengupta & Karmakar, 2004). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tips of human digits are characterized with genetically and environmentally determined series of ridges and furrows, generally referred to as fingerprints (Cummins and Midlo 1943;Holt 1952;Holt 1968;Schaumann and Alter 1976;Reed et al 2006). Development of epidermal ridges is first seen in the 10 th -11 th weeks of gestation and is marked by cell proliferations in the basal layer of the epidermis (Mulvihill and Smith 1969;Babler 1978).…”
Section: Introductionmentioning
confidence: 99%
“…This detail is not specific enough to be applied for personal identification. It is mainly used by biological anthropologist to differentiate between population (Arrieta et al 2003;Scheil et al 2005;Dorjee et al 2015) and for the determination of heritability, ethnicity, and sex (Reed et al 2006;Adamu et al 2016). Level 2 features called minutiae refer to the shape, direction, and orientation of the trait that forms the friction ridges, and is used mainly for the purpose of establishing identity (Langenburg 2004;Nickell and Fischer 1999;Bennett and Perumal 2011).…”
Section: Introductionmentioning
confidence: 99%